Regional Economic Outlook, October 2007, Middle East and Central Asia. (Regional Economic Outlook, 2007)
The Middle East and Central Asia is undergoing a remarkable transformation driven by rapid GDP growth and high oil and non-oil commodity prices. The report presents common economic trends and reviews prospects and policies for the coming year in light of the global economic environment. This latest REO includes boxes treating both regional topics--such as growth in the Maghreb countries; developments in the oil markets; the boom in the GCC countries, and the impact of the recent global credit squeeze on the region--and country-specific reviews, of Kazakhstan, Armenia, Egypt, Pakistan, and the UAE.